The Governance Reform In The Coaching Services Of Prisoners In The Correction Centers (A Study At The Sukamiskin Class I Correction Center) - Agung Edi Rustanto; Teguh Sandjaya; Wuwuh Andayani (Universitas Padjadjaran, 2023)
In general, the problems of LAPAS in Indonesia are regarding overcapacity and facilities that are not up to standard. However, in Class 1 Sukamiskin LAPAS, among other problems, there are interesting problems to study after the reform. The purpose of this study was to analyze coaching services after governance reform was carried out at Class 1 Sukamiskin Correctional Institution. What improvements have occurred in coaching services at Class 1 Sukamiskin LAPAS need to be studied in more depth because coaching is a very important service. Some aspects of the coaching carried out in governance reform at Class 1 Sukamiskin prison are coaching in the form of spiritual activities, fulfillment of remission rights, assimilation, parole leave, parole, and leave before release, and sports activities. Governance reform at Class 1 Sukamiskin LAPAS was carried out through several effective stages. The success of governance reform in coaching services needs to be investigated because it is very important to know the implementation process. This research uses a descriptive qualitative method with a case study approach at Sukamiskin Class 1 LAPAS. Informants in this study were LAPAS leadership officials, LAPAS staff officers, prisoners and visitors. The results of this study are that there is an increase in coaching services in the form of spiritual activities, an increase in the fulfillment of remission rights, assimilation, parole leave, parole leave, and leave before being released online, the implementation of sports activities becomes more systematic and directed. The results of this study indicate that there is a positive impact from governance reform in Class 1 Sukamiskin LAPAS being able to realize an increase in coaching services through organizational structure changes and change management.